2019
DOI: 10.1051/e3sconf/201912205007
|View full text |Cite
|
Sign up to set email alerts
|

Study of the destructive activity of microorganisms isolated from soil contaminated by pesticides

Abstract: Chemical pollution of natural and agricultural habitats is a growing global problem and a serious threat to the sustainability and health of people. Among various chemical ecotoxicants of anthropogenic origin, organochlorine pesticides are among the most stable and dangerous for the environment and humans. Pesticides are chemical plant protection products, the intensive and not always justified the use of which has led to the fact that recently they are also considered among the most dangerous pollutants. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…At environment-related concentrations, the high accumulation in tissues interferes with the ability of metabolism and thyroid endocrine system and leads to more serious liver damage [9] . Intensive use of pesticides is not always reasonable [10] . Studies in Tibetan alpine grasslands in Qinghai have shown that soil parameters and salts (such as phosphorus) may affect microbial diversity and function, and pesticide pollution leads to a decrease in microbial diversity richness [11] .…”
Section: 23harm To Animals and Microorganismsmentioning
confidence: 99%
“…At environment-related concentrations, the high accumulation in tissues interferes with the ability of metabolism and thyroid endocrine system and leads to more serious liver damage [9] . Intensive use of pesticides is not always reasonable [10] . Studies in Tibetan alpine grasslands in Qinghai have shown that soil parameters and salts (such as phosphorus) may affect microbial diversity and function, and pesticide pollution leads to a decrease in microbial diversity richness [11] .…”
Section: 23harm To Animals and Microorganismsmentioning
confidence: 99%